Ferro-ferri-hornblende from the Traversella mine (Ivrea, Italy): occurrence, mineral description and crystal-chemistry. (2nd January 2018) - Oberti, Roberta; Boiocchi, Massimo; Hawthorne, Frank C.; Ball, Neil A.; Cámara, Fernando; Pagano, Renato; Pagano, Adriana
Abstract: Ferro-ferri-hornblende is a new member of the amphibole supergroup (IMA-CNMNC 2015-054). It has been found in a rock specimen from the historical collection of Leandro De Magistris, which was collected at the Traversella mine (Val Chiusella, Ivrea, Piemonte, Italy). The specimen was catalogued as 'speziaite', and contains a wide range of amphibole compositions from tremolite/actinolite to magnesio-hastingsite. The end-member formula of ferro-ferri-hornblende is A □ B Ca2 c (Fe + Fe 3+ ) T (Si7 Al) O22 W (OH)2, which requires SiO2 43.41, Al2 O3 5.26, FeO 29.66, Fe2 O3 8.24 CaO 11.57, H2 O 1.86, total 100.00 wt.%. The empirical formula derived from electron microprobe analysis and single-crystal structure refinement for the holotype crystal is A (Na0.10 K0.13 )Σ=0.23 B (Ca1.93 Na0.07 )Σ=2.00 C (Mg1.16 Fe 2+ 3.21 Mn0.O6 Fe3+ 0.45 Al0.12 Ti0.01 )Σ=5.01 T (Si7.26 Al0. 74 )Σ=8.00 O22 W (OH1.89 F0.01 C10.10 )Σ=2.00 - Ferro-ferri-hornblende is biaxial (-), with α = 1.697(2), P = 1 .722(5), γ = 1.726(5) and 2V (meas.) = 35.7(1.4)°, 2V (calc.) = 43.1°. The unit-cell parameters are a = 9.9307(5), b = 18.2232(10), c = 5.3190(3) Å, β = 104.857(1)°, V= 930.40 (9) Å 3, Z= 2, space group C2/m. The a:b:c ratio is 0.545:1:0.292. The strongest eight reflections in the powder X-ray pattern [ d values (in Å), I, (hkl)] are: 8.493, 100, (110); 2.728, 69, (151); 3.151, 47, (310); 2.555, 37, ( ); 2.615, 32, (061); 2.359, 28, ( ); 3.406, 26, (131); 2.180, 25, (261). Type material is deposited in the collections of the Museo di Mineralogia, Dipartimento di Scienze della Terra e dell'Ambiente, Università di Pavia, under the catalogue number 2015-01. Sample M/U15285 from the historical collection of Luigi Colomba, presently at the Museo Regionale di Scienze Naturali di Torino, was also checked, and the presence of ferro-ferri-hornblende was confirmed.